Implementation of Restorative Justice in the Criminal Justice System: A Comparative Study between Indonesia and India - Hamzani, Achmad Irwan; Loso, Loso; Bhanu Prakash Nunna (Universitas Negeri Semarang, 2025)
Restorative Justice has emerged as a progressive response to the limitations of the retributive approach within criminal justice systems. Both Indonesia and India demonstrate a growing inclination toward adopting Restorative Justice as a more humanistic mechanism for social restoration. This study aims to analyze and compare the policies and implementation of Restorative Justice in Indonesia and India, while highlighting the challenges and opportunities for its development. The research employs a normative legal method with a comparative and qualitative approach, using secondary data in the form of legal documents and scholarly articles, analyzed through online content analysis techniques. The findings indicate that both countries share fundamental principles of Restorative Justice, such as victim participation, mediation, and the restoration of social relationships. However, there are significant differences in legal frameworks, procedural flexibility, and institutional support: Indonesia demonstrates greater adaptability to local and community values, whereas India remains largely confined to the juvenile justice system and reliant on judicial discretion. This study offers a novelty in the form of a comprehensive mapping of the normative and structural dynamics of Restorative Justice within the South and Southeast Asian contexts, which have been underexplored in comparative legal research. The implications underscore the need for strengthening national regulations and institutional synergy as critical prerequisites for the sustainable implementation of Restorative Justice. The study also recommends the development of a flexible, community-based institutional model to advance criminal justice systems toward more inclusive, transformative, and participatory justice.